The Canadian experience of the Great War : a guide to memoirs - Tennyson, Brian Douglas (The Scarecrow Press, Inc, 2013)
Although the United States itself did not enter the war until April 1917, Canada enlisted the moment Great Britain engaged in the conflict in August of 1914. The Canadian contribution was great, as over 600,000 men and women came to serve in the war effort. Over 150,000 were wounded while near 67,000 gave their lives. The literature it generated, and continues to generate so many years later, is enormous and addresses all of its aspects. The Canadian Experience of the Great War: A Guide to Memoirs is the first attempt to.